Application of screw reinforcement in the slotted-in bamboo-steel-bamboo connections. (October 2021) - Li, Z.; Wang, C.; Wang, R.
Abstract: This research presents the mechanical performance of self-tapping screw-reinforced slotted-in bamboo-steel-bamboo (BSB) connections and the corresponding capacity models. The yield strength of self-tapping screws (STS) and bolts commonly used in practical constructions were obtained through the three-point bending tests. The withdrawal tests of the screws from the engineered bamboo panels were reported. The BSB connections using STS reinforcement in different positions were studied, and the performance and mechanical parameters were compared with the connections without reinforcement. The test results show that STS application in the BSB connections can significantly improve its ductility and bearing capacity. Compared with the connection without STS reinforcement, the bearing capacity and ductility of the reinforced connection with STS reinforcement near the top were increased by 8% and 3.8 times. For STS application near the bottom and at both ends, the increased values were 26% and 4.3 times, 35% and 4.6 times, respectively. The brittle row shear failure mode of the unreinforced BSB connections can be changed to be the ductile yielding failure modes by applying STS reinforcement reported in this study. Based on the existing theoretical models, the capacity predictions of the BSB connections based on two different failure modes were calculated and compared with the test results. According to the experimental research conducted in this paper, it is strongly recommended that the STS reinforcement be used in the unidirectional bamboo connections to confirm the ductile failure modes, which can be estimated through the well-established European Yield Model (EYM) included the current design standards.